(untitled) (The International Journal for Scientific Research, 2024)
Operations play a major role in the LPG industry where the business involves suppliers, some of who are the business owners and customers. Organizations in the LPG industry are faced with challenges in their quest to deliver their products to consumers while concurrently ensuring profitability. Thus, they have to tailor their business operations practices to fit the market. This scientific research aims to see to what extent operations management practices are being undertaken in the National Gas and Industrialization Co. (GASCO) headquarter in Riyadh city that also it owns seven (7) filling stations and a transportation and distribution fleet in Saudi Arabia by studying their supply chain and their process to determine how they impact on the operational performance of the factories. The target population in this study was the National Gas and Industrialization Co. (GASCO) headquarter in Riyadh city that also it owns seven (7) filling stations and a transportation and distribution fleet in Saudi Arabia. Primary data on the project implementation was collected using a questionnaire. Secondary data was obtained from relevant publications and literature review from the different organizations. Data was presented using tables, and pie charts to make them reader friendly and this study conducted a multiple regression analysis. Multiple regression analysis was used to establish the relationship between the independent and dependent variables. The study found that there is a positive significant relationship between supply chain, lean management, value stream mapping, machine maintenance and operational performance. However, the study found a negative relationship between constraints and operational performance of an organization. The study recommends that factories should be urged to adopt all the practices under supply chain management, adoption of communication channels enhancement among all the staff working in various departments to improve value stream mapping. The study further, recommends that National Gas and Industrialization Co. (GASCO) headquartered in Riyadh city that also it owns seven (7) filling stations and a transportation and distribution fleet in Saudi Arabia should have a skilled LPG manpower to handle issues on machine maintenance and replacement as this will lead to continued production.